Revitalisasi Kemaslahatan Koperasi di Indonesia: Pendekatan Maqashid Syariah dan Wellbeing Methodology - Rusdi Tahir; Ikhsan Gasali (J-Coop : Journal of Co-operative, 2026)
This study aims to analyze the revitalization of cooperatives in Indonesia through the maqashid syariah approach and wellbeing methodology. The focus of the study is on developing a Public Wellbeing Index (IKP) for cooperatives that not only assesses financial aspects, but also dimensions of morality, ethics, and social values. The research methods used are literature study, interviews, field observations, and Expert Group Discussion (EGD) to select critical success factors (CSF) variables. The results of the study show that cooperatives cannot be adequately measured using conventional economic indicators; rather, they must take into account aspects of public welfare. The IKP developed in this study can serve as a new evaluation tool, relevant to the objectives of sharia law to achieve justice and prosperity.